Chungrung- mithun cattle hybrid: A Boon for Mishmi Tribes of Arunachal Pradesh - Tayo, Tilling; Kanwat, Manish; Longjam, Neeta; Mahanta, Prasanta (Indian Journal of Hill Farming, 2019)
Species hybridization between Mithun and Cattle is a form of outbreeding, to produce new offspring locally called as Chungrung by Digaru Mishmi, is a natural paradigmatic shift towards positive development of new breeds (Chungrung). Thereby, improving the low face value animal (cattle) to high face value animal (Chungrung), without much human manipulation against the desire of both the animals. However, there is a dilution in pure germplasm of both the species. Nevertheless, species hybridization is a boon for Mishmi society, because as per tradition and customary law and practices, Chungrung is considered at par with Mithun status in Mishmi society. Adult Mithun and Hybrid animal (Chungrung) cost around Rs 60,000 – 80,000, in counterpart adult cattle cost around 15,000 – 20,000 only. Consequently, Mithun and Chungrung is consider as most blessed animal for livelihood sustenance in many different dimension be it in social, culture or religious aspect of Mishmi society in Arunachal Pradesh.